Emprego de modelos Euleriano no estudo da dispersão de contaminantes na camada limite planetária - Ferreira, Cecilia Perobelli (2016)
The transport models and dispersion of contaminants in the atmosphere are mathematical tools extremally useful at prediction and evaluation of concentration of pollutants issued by di erent polluting sources. Theses models shoud describe basically the trajectory average travel of contaminants and it is di usion caused by e ect of the turbulence present in the planetary boundary layer. In this work the Eulerian models used to study the dispersion of contaminants. In this models the dispersion of contaminants will be considered in a xed point in space and its magnitude will be proportional to the local concentration gradient of the dispersed material. In this investigation is employed the Taylor's di usion model and turbulent energy spectra to derive the turbulent di usion coe cients in di erent stability conditions of planetary boundary layer. These parametrizations of K are substituted in equation of the Eulerian model to simulate and reproduce the observed concentrations of pollutants. The results of the simulations show that the Eulerian model, solved by the semi-analytical solution GILLT and applied to stable conditions in which the turbulence is generated by win shear, presents concentrations that reproduce satisfactorily the concentration of contaminants observed in the Hanford experiment. In addition, the di usion-advection model solved numerically using the nite di erence method, generated concentrations which reproduced reasonably well the concentrations observed in the Copenhagen experiment.